Evaluation of the Phytotherapeutic Potential of the Passiflora Species in the Management of PCOD Symptoms - Madhavan, Priyadarshini; Chhetri, Dikhsha; George, Joanne Roji; Umesh, Nishal; Jha, Priya; Babu V L, Ashoka; Nayak, Damodar (Journal of Neonatal Surgery, 2025)
Polycystic Ovary Disease (PCOD) is a common endocrine and metabolic disorder in reproductive- aged women, often managed with pharmacological agents that carry adverse effects. This study evaluates the phytotherapeutic potential of Passiflora foetida and Passiflora incarnata ethanolic extracts in a letrozole-induced PCOD rat model. Aerial parts of both species were extracted using ethanol, and PCOD was induced in female Wistar rats (n = 30) through oral administration of letrozole (1 mg/kg/day for 21 days). Animals were assigned to five groups: normal control, disease control, metformin-treated (300 mg/kg), P. foetida (300 mg/kg), and P. incarnata (300 mg/kg), followed by a 28-day treatment period. Serum levels of LH, FSH, and testosterone were measured alongside body weight and histopathological assessments of the ovary, uterus, and liver. Molecular docking and ADMET analysis were also performed on key phytoconstituents. Treatment with both Passiflora species significantly restored hormonal balance (p < 0.001), reduced pathological weight gain, and improved histoarchitecture, with P. foetida demonstrating superior efficacy. Docking results revealed high binding affinities for vitexin (−9.83 kcal/mol) and luteolin (−9.53 kcal/mol), surpassing that of metformin (−5.43 kcal/mol), while ADMET predictions indicated favorable absorption and safety profiles. These findings support the therapeutic potential of Passiflora species—particularly P. foetida—as natural alternatives for PCOD management, warranting further clinical investigation.